'Austrofaschismus' und moderne Faschismusforschung. (4th May 2021) - Simon, Thomas
ABSTRACT: This article examines the character of the political system which was introduced in Austria in 1933 mainly by the Austrian Chancellor Engelbert Dollfuß and his followers in the Christlichsoziale Partei. Without doubt this 'Autoritäre Ständestaat', as it was called by its political architects in the Christlichsoziale Partei, was a dictatorial system established by the means of a coup d'état against the democratic parlamentary system of 1918–20. But was it also a fascist system? This article deals with the question whether the political system in Austria between 1933 and 1938 can be described as a 'fascist' one. To answer this question two approaches have been applied. The first approach compares the Austrian dictatorship with the large number of dictatorial systems which arose in the newly established states in Central Eastern Europe in the interwar period. The starting point of the second approach is the modern theory of fascism. The current discourse about the term 'Faschismus' will briefly be outlined and can then be applied at the 'Austrofaschismus'. Both approaches lead to the same result: Under no circumstances can the Austrian Dictatorship of the 1930s be described as a fascist system. Rather it was one of those authoritarian systems which were typical in Central Eastern Europe in the interwar period. This article builds on the preceding article in this volume 'Der "autoritäre Ständestaat" in Österreich und die Diktaturen im Osteuropa der Zwischenkriegszeit'.